ARANG HAYATI DAN TURUNANNYA SEBAGAI STIMULAN PERTUMBUHAN JABON DAN SENGON - S. Komarayati; G. Pari (Universitas Tribhuwana Tunggadewi, 2012)
Biological biochar is potential carbon storage in the soil that can increase soil fertility. The aim of this study was to evaluate utilization of saw dust biochar, compost biochar and wood vinegar on growth of Jabon and Sengon seedlings. The result showed that addition of saw dust biochar, mix biochar, wood vinegar, and compost biochar increased height of seedlings by 5%, 5%, 2%, and 10%, respectively. For seedling stem, addition of saw dust biochar and compost biochar increased the diameter by 5% and 10%, respectively. Concentration ratio of saw biochar of 5%, mix biochar of 5%, wood vinegar of 2% and compost biochar of10% were suitable to increase growth of jabon and sengon seedlings